PENGARUH PUPUK BOKASIH TERHADAP PERTUMBUHAN, HASIL, SERTA SIFAT FISIK DAN KIMIA TANAH PADA TANAMAN CABAI (Capsicum annuum L.) - Julianus Jeksen (Agriculture Faculty of Flores University, 2013)
This study was conducted to determine the effect bokashi fertilizer on the growth and yield of pepper plants, soil physical and chemical properties as well as the optimum dose of fertilizer bokashi. The design used in this experiment is a randomized block design (RAK) to the single factor pattern consisting of five treatments, namely: B0: 0 tonnes ha-1, B1: 5 tonnes ha-1, B2: 10 ton ha-1, B3: 15 ton ha-1 and B4: 20 tonnes ha-1. The variables were observed in this study is was a high plant (cm), a number of leaves tan-1 (strands), leaf area (cm2), fresh weight of fruit tan-1 (g tan-1) and ha-1 (ton ha-1 ), the soil volume weight (bulk density) (g cm-3), total soil pore space (%), total soil N, P-available land, available K-land, C-organic soil and soil pH. The results showed a significant influence on the variable crop growth and yield of pepper plants. Bokashi fertilizer application also provides improved physical and chemical properties of soil. Bokashi fertilizer use 20 tonnes ha-1 is the optimum dose that increases the weight of fresh chilli ha-1 as much as 26.63 tons.